Journal of Toxicology & Environmental Health Part A: Current Issues - Journal of Toxicology & Environmental Health Part A: Current Issues (Taylor & Francis, 2026)
The journal aims to emphasize the toxicological effects of natural and anthropogenic environmental pollutants and their actions on both intact organisms and in vitro systems. From a public perspective, another focus of the journal is the results of epidemiological studies on affected consumers and select groups of occupational workers.
FI 0.71
Q3
Keywords: Biological; Earth & Environmental Food Science; Acuerdos transformativos; Transformative agreements; Clima urbano; Isla de calor urbana; Calidad del aire; Sostenibilidad urbana